Sputum viscosity: correlation with chemical and clinical features in chronic bronchitis - Lopez-Vidriero, Maria Teresa (1973)
Lopez-Vidriero, M.T., Charman, J., Keal, E., de Silva, D. J., and Reid, L. (1973).Thorax, 28, 401-408. Sputum viscosity: correlation with chemical and clinical features in chronic bronchitis. A series of out-patient chronic bronchitics with severe airways obstruction was studied monthly over a five-month period from December 1970 to May 1971; volume, pourability, viscosity, and chemical constituents of sputum, the patients' FEV(1·0)/VC%, and viral antibodies were measured. Mucoid sputum showed a highly significant correlation between pourability grade and viscosity. The mean coefficient of variation for each feature studied was between 13 and 17% for pulmonary function tests and between 25 and 44% for sputum estimations. Significant inverse correlations were found between sputum volume and viscosity, dry weight yield, neuraminic acid (NANA), and fucose, and a positive correlation with FEV(1·0)/VC%. Linear correlations showed that mucoid sputum dry weight yield correlated with NANA and fucose concentrations, viscosity with NANA, dry weight, and fucose, in ascending order of significance. Mucopurulent sputum viscosity correlated to a much less degree with NANA. Second order partial correlation coefficients showed that for mucoid sputum viscosity was affected equally by dry weight and fucose but not by NANA: for mucopurulent sputum fucose was twice as influential as dry weight while NANA showed an inverse correlation with viscosity (probably because of degradation of NANA). Taking all patients and samples together, a significant inverse correlation was found between sputum viscosity and absolute values of FEV(1·0) and FEV(1·0)/VC%, and between FEV(1·0)/VC% and NANA. Seven patients showed considerable monthly changes in sputum viscosity, NANA, and fucose concentrations, which were high in December and in February or March, coinciding with peaks in atmospheric smoke and sulphur dioxide. No patient showed any evidence of viral infection.